La gimnasia y las capacidades físicas - Sinchiguano Panchi, Cesar David (2017)
This research had as an objective to diagnose the influence of the artistic gymnastics in the development of the physical capacities and improve the development of the same, with the implementation of the gymnastics and its different sections in the school environment which it will be the lots of help for students in Maria Ines Endara School, that it will allow to progress in the Physical Education activities so that the students can develop their skills through strategies, resources and materials in the learning teaching process, also it will help to motivate students in Physical Education classes to get the meaning of respecting the environment and the other ones at the end of this school year. By means of the artistic gymnastics, I can see that students don’t have a good development in their abilities and skills in order to improve their quality of life in the schools. In this investigation I used the inductive, deductive and statistics method which it helped to develop this project. I recollected the necessary information through poll and it gave as a result that students found available in the development of the project, with the improvement of their physical capacities….